Clinical and Demographic Profile of Acute Anterior Uveitis: A Hospital Based Study - Gurung, Anu; Shrestha, Dhan Bahadur; Budhathoki, Pravash; Dhakal, Sachit; Rajkarnikar, Sagar; Thapa, Kamala; Shrestha, Ram (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Uveitis is an inflammatory condition of uvea of eye. It is a sight threatening condition, so accurate and timely diagnosis and treatment is required. Acute anterior uveitis is characterised by eye pain or photophobia, circumlimbal redness and anterior chamber cells and flare. Methods: This is a cross-sectional descriptive hospital record-based study based on data record in eye department of a tertiary care level centre in Kathmandu, Nepal. All cases of anterior uveitis presented to our OPD over one-year duration (December 2017- November 2018) were enrolled. Age, sex, co-morbidities and profile of uveitis like slit lamp findings were recorded. Results: Total 52 cases of acute uveitis were observed during the study period. There were total 34 males and 18 females with eye involvement. Age group of the patients ranged from 19 to 79 years with median age of 36 years. Forty eight cases (92.3%) had unilateral involvement whereas only four cases (7.7%) had bilateral involvement. Keratic precipitates were seen in 44 patients. Majority of the patients had good vision; 65.4% in right eye and 69.2% in left eye. Conclusions: Most of the anterior uveitis occur in male in third and fourth decade. The most common complaints of the patient were decreased vision, eye pain and red eye.